2004
DOI: 10.1530/rep.1.00053
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3 (Stat3) expression and activation in rat uterus during early pregnancy

Abstract: Signal transducer and activator of transcription 3 (Stat3), a member of the Stat family, is specifically activated during mouse embryo implantation. The aim of this study was to investigate the expression, activation and regulation of Stat3 in rat uterus during early pregnancy, pseudopregnancy, delayed implantation and artificial decidualization. Stat3 mRNA was highly expressed in the luminal epithelium on day 5 and in the luminal epithelium and underlying stromal cells at implantation sites on day 6 of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Our findings that Stat3 is expressed at high levels in the reproductive tissues suggest that Stat3 may play a role in the regulation of reproductive function. The presence of Stat3 protein in the mucosal folds of the oviduct, and the endometrium of the uterus is consistent with the previously reported role of Stat3 during early embryogenesis (Takeda et al 1997), implantation and development (Teng et al 2004a(Teng et al , 2004b. It is possible that the expression of Stat3 in the oviduct and uterus is involved in upregulating the expression of genes that are important for early embryo development and implantation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings that Stat3 is expressed at high levels in the reproductive tissues suggest that Stat3 may play a role in the regulation of reproductive function. The presence of Stat3 protein in the mucosal folds of the oviduct, and the endometrium of the uterus is consistent with the previously reported role of Stat3 during early embryogenesis (Takeda et al 1997), implantation and development (Teng et al 2004a(Teng et al , 2004b. It is possible that the expression of Stat3 in the oviduct and uterus is involved in upregulating the expression of genes that are important for early embryo development and implantation.…”
Section: Discussionsupporting
confidence: 90%
“…Stat3 is essential during embryogenesis, given that disruption of the mouse Stat3 gene is embryonic lethal at approximately E6.5-7.5 (Takeda et al 1997). Stat3 also plays an important role in mouse and rat reproduction during implantation and decidualization (Teng et al 2004a(Teng et al , 2004b. Additionally, it has recently been reported that leptin regulates porcine ovarian granulosa cell function via the JAK/STAT pathway (Ruiz-Cortes 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed STAT3 is specifically activated during mouse and rat embryo implantation (10,42) and in human endometrial stromal cells during decidualization (43). Recent studies characterized STAT3 as a regulator of differentiation in human stromal cell decidualization (44).…”
Section: Estrogen Is a Key Regulator Of Egr1 Expression In Uterine Stmentioning
confidence: 99%
“…In the other hands 398 in our study condition the lower cleavage rate, as a consequence of 399 oocyte cryopreservation, might be associated with a cytoplasmic 400 incompetence, including lack of oogenetically derived molecules 401 necessary for initiating embryogenesis [14,28,50]. 402 As shown ( implantation and decidualization [45,46]. (Table 2).…”
Section: Oocytementioning
confidence: 58%
“…Moreover, in contrast to CDH1 the relative expression of STAT3 in vitri-43 fied derived embryos was higher than embryos derived from fresh oocytes. The overexpression of STAT3 44 in embryos derived from vitrified oocytes might be the reason for the lower CDH1 expression and in turn 45 the lower developmental competence of the resulting embryos.…”
mentioning
confidence: 99%